The TERARIUM MEDIA IN THE LEARNING PROCESS - Nooryani Nooryani; Makrina Tindangen; Candra Candra (Program Pascasarjana Universitas Negeri Jakarta, 2021)
The purpose of the study was to find out the problems faced by teachers when developing terrarium media. This study uses a quantitative approach with percentage data analysis method and analyzed descriptively. The results show that the problems faced by teachers when developing terrarium media to improve the entrepreneurial skills of high school students are still very many and it is necessary to carry out an innovation that can accelerate educational innovation at the high school level in Samarinda City. this is corroborated by the results of observations that have been made in several high schools in the city of Samarinda, analyzed and then presented, so that 70% of teachers have not been able to develop terrarium media that are relevant to the material to be delivered, this is due to the lack of teacher knowledge regarding terrarium media which has economic value. It can be concluded that it is necessary to carry out new innovations to improve the entrepreneurial abilities of high school students.